Heavy metals assessment (Fe, Zn, Mn) in vegetables planted at different topographical area: a review / Norain Mohamed - Mohamed, Norain (Faculty of Plantation and Agrotechnology, 2019)
Heavy metals toxicity is gaining much concerns nowadays due to its hazardous effects on environment and human health. Due to its harmful effects, this study intends to review the concentration of heavy metals (limited to Fe, Zn and Mn) in different topographical area which has been planted with different types of vegetables. The review showed that much of the studied heavy metals were concentrated in leafy vegetables planted on low land area. It is suggested that the factors including the pesticide residues as well as the soil geographical area plays important roles in accumulation of heavy metals at low land area.